Chondroitin in Transdermal Patch and Its Main Physical Properties - Sopyan, Iyan; Tedjasaputra, Moeljadi G; Utami, Saskia Rizky; Abdassah, Marline (Indonesian Journal of Pharmaceutical Science and Technology, 2017)
Chondroitin sulphate (CS) in oral dosage form has widely used to help manage osteoarthritis, but regret its bioavailability was very low at only 13%, It was due to the first passed effect in the liver and to avoid it CS is needed to be formulated into another forms of preparation like patch. This study was aimed to gure out in-vitro possibility of chondroitin sulphate (CS) to be formulated in a transdermal patch and characterized by its physical properties such as permeation profile through the Franzâs cell and partition coefficient studies. The study showed that 150 mg CS in transdermal patch given the constant permeation within 19 hours with the partition coefficient of 2.22. Based on the permeation profile and the partition coefficient study, the CS patch would become an effective preparation to be considered.Keyword : Chondroitin Sulphate (CS), Transdermal patch, Permeation profile, Partition coefficientÂ